Outcomes Of Open Prostatectomy and Early And Late Complications In The Treatment Of Benign Prostate Hyperplasia - نعوس علاء; خضر رسلان; حسان ناصر (Latakia University Journal -Medical Sciences Series, 2023)
* Objective: The aim of the research to evaluating the results and complications of simple surgical prostatectomy through the bladder and deducing the relationship of the results and complications to the size of the prostate and comparing it with similar international studies among patients attending Tishreen University Hospital in the period from 1/1/2019 to 12/31/2021. * Methods: Study type A retrospective observational study. Place: Department of Urology, Tishreen University Hospital, Lattakia.The research sample consisted of (68) cases of benign prostatic hyperplasia, large in size greater than or equal to 80 g, who are scheduled to undergo surgery, recorded clinical, radiographic and laboratory investigations before surgery, performed open prostatectomy through the bladder, and divided the patients according to the weight of the prostate into three groups, the first (less than 100 g). the second (100-125g) and the third (more than 125g). And study the results and complications in each group to find out the relationship of the results and complications with the size of the prostate, and compare the results and the overall complications of the study with the global results and complications. * Results: The number of patients in the study was 68 patients, most of whom were between ages (50-70 years). The mean IPSS before surgery was (25.34 ± 4.9), and the mean IPSS after surgery was (5.4 ± 2.9). The patients were distributed into groups according to the weight of the prostate, 42 patients in the first group (less than 100g), 23 patients in the second group (100-125g), 3 patients in the third group (more than 125g). Outcomes and complications were evaluated in each of the three groups. No difference was observed in the results of surgery in the three groups, and the proportion of a large group of complications after surgery was directly proportional to the size of the prostate. Conclusions: Open surgical removal of the prostate through the bladder is considered one of the important treatments for benign prostatic hyperplasia used in our country, and its complications are directly proportional to the size of the prostate.